Leading Local Economic Development in the ‘New’ Normal: Urban and Rural Challenges in the Case of a District Municipality in KwaZulu-Natal, South Africa - AYANDA MAKHAYE; MOGIE SUBBAN (African Journal of Governance and Development, 2024)
South Africa’s economic performance has been negatively impacted by factors including political instability, protests, power outages, and natural disasters, leading to economic decline and difficulty in recovery thereof. Small businesses and municipalities, especially in remote areas, face significant losses and struggle to recover. Local Economic Development (LED) in the country is crucial for economic growth and job creation. However, challenges such as corruption, political interference, capacity limits, and lack of funding hinder successful implementation of LED. This paper focuses on difficulties faced by municipalities, necessitating them to implement resilience methods to adjust to current situations. It explores the tremendous changes caused by the pandemic, analysing its influence on several aspects of society and the local economy. The study conducted in the uMgungundlovu District Municipality in KwaZulu-Natal, examined challenges faced by stakeholders in implementing LED with emphasis on the need to enhance resilience to address challenges in the 'new' normal. Through qualitative analysis, the research engaged LED practitioners using interviews to gain insights into their lived experiences and issues affecting LED implementation. The findings suggest the need for enhancing urban and rural resilience through adopting adaptive strategies and facilitating stakeholder collaborations as key factors for the district to address these challenges.